Pemanfaatan Limbah Ampas Tahu Menjadi Nilai Ekonomis di Desa Bendosari Kediri - Sagita, Dhisa; Shofia, Syafna Malikhatus; Putri, Refy Salvia; Yulianingsih, Rizki Eka; Diniati, Bintis Tianatud (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Bendosari Village is one of several villages located in Kras District, Kediri Regency. In Bendosari Village, Kediri, there is a tofu production industry. The purpose of this research is to reveal how the empowerment of tofu pulp waste into economically valuable products in Bendosari Village, Kediri. In its processing, tofu must produce quite a lot of waste such as tofu pulp waste. If this waste is not managed, it will become pollution for the environment. However, tofu pulp waste can be utilized to become one of the raw materials in producing products of economic value, this is beneficial for the people of Bendosari Village. This research used a qualitative approach. Data collection was carried out using observation, interview, and documentation methods. The results show that the empowerment process is in the form of training and coaching on how to turn tofu pulp into many products such as animal feed. This effort not only has a positive impact on the local economy, but also supports environmental sustainability by reducing wasted waste. It is hoped that this research can be a reference for the development of waste-based creative economy programs in other areas.